Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Tanggung Jawab dan Hsil Belajar Siswa - Ursula Yula; Herry Sanoto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was motivated by the low results of responsibility and learning outcomes in Natural Sciences subject matter of Style and Movement of fourth grade students of SD Negeri 05 Senakin, Sengah Temila District, Landak Regency. The purpose of this study was to determine the increase in responsibility and learning outcomes in the subject matter of Force and Motion in Natural Sciences through the application of the Problem Based Learning (PBL) learning model. This type of research uses Classroom Action Research (CAR) and the steps of planning, implementing, observing and reflecting. This Classroom Action Research was carried out in two cycles, each cycle carrying out 2 times. The learning outcomes of students in cycle I were 75 with classical completeness of 46.42% (13 students) who achieved a score of â‰¥65 (KKM score). Cycle II students' learning outcomes were 82.66 with classical completeness of 85.71% (24 students) who achieved a score of â‰¥65 (KKM score). It can be concluded that the application of the Problem Based Learning (PBL) learning model can increase the responsibility and learning outcomes of students, the learning content of Natural Science class IV Elementary School. Keywords: Responsibility, Learning Outcomes, Problem Based Learning, Science